HUBUNGAN TINGKAT STRES DENGAN KEJADIAN HIPERTENSI PADA KELOMPOK RESIKO TINGGI HIPERTENSI DI WILAYAH KERJA PUSKESMAS KUMELEMBUAI - Glorya Saroinsong; Agusteivie Telew; Vera Tombokan (Yayasan Syalom Cipta Sumikolah, 2024)
Stress is a physical and emotional reaction of a person to environmental changes that require adjustment. Hypertension is a condition where there is an abnormal and persistent increase in blood pressure, caused by risk factors that do not function properly in maintaining normal blood pressure levels. This research aims to determine the relationship between stress levels and the incidence of hypertension in high-risk groups in the working area of the Kumelembuai Community Health Center. This research uses a cross-sectional design and was conducted in Paslaten Village, Minahasa Regency. The instrument used is the Depression Anxiety Stress Scales questionnaire. (DASS 42). Data analysis was conducted using the chi-square test. The research results indicate that 44.2% of respondents experienced low stress, 55.8% experienced moderate stress, and no respondents experienced high stress. A total of 93% of respondents had stage I hypertension, while 7% had stage II hypertension. The chi-square test results showed a p-value of 0.044, which means there is a significant relationship between stress levels and the occurrence of hypertension in the high-risk hypertension group in the working area of the Kumelembuai Community Health Center.